Peningkatan Motivasi Belajar dan Kemampuan Berpikir Kritis Peserta Didik Menggunakan Model Think Pair Share Berbantuan Alat Peraga Bahan Bekas - Nurul Hidayah; Witri Anisa (AR-RIAYAH : Jurnal Pendidikan Dasar, 2019)
The purpose of this study is to improve students' motivation and critical thinking skills through think pair share model that is supported by used materials. Critical thinking ability is needed by students to be able to solve problems. To measure students’ motivation, this study used questionnaires and to measure students' critical thinking skills, this study applied a test. The results show that from the average score of motivation, students' learning motivation reaches 59.8% in the first cycle of study and this proves that there is no significant improvement in students’ motivation. Then, it increases up to 78,6 in the second cycle and 86.7% in the third cycle which means that students’ motivation increases significantly. In relation to students’ critical thinking skills, it is seen that there is a significant improvement in each skills, in which the average score of the test in cycle I is 54,2% and it increases up to 65,7% in cycle II and 83,8% in cycle III with the achievement score of 85%. From these results it can be concluded that there is an increase in students’ learning motivation and critical thinking skills through think pair share models supported with used material.